Ludruk Jawa Timur, Budaya Perlawanan yang Tersisih oleh Budaya Media - Adicahyo, Agustinus Lintang (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2014)
The very fast development of media culture nowadays has prompted a significant impact on the existence of ludruk. With their creativity performed on their shows, the ludruk artists have created a product of culture which is in contrast to the common trends of the time, such as in the colonial era, a resistance and various kind of satires against the colonialists and in the modern era against the negative trends in the society. The writer considers that ludruk, as the product of culture of the time is always expressing its critiques againts the condition of the time. Todays ludruk as a performance art has been marginalised or pushed aside due to the fast development of the mass culture. Performance art of ludruk could no longer catch the interest of this generation; it has been substituted by the modern media, which is much more pupular, relatively cheaper, and more easily consumed via television or any other kinds of electronic equipments.